Survival Strategies of Mangrove (Ceriops tagal (perr.) C. B. Rob) and the Inspired Corrosion Inhibitor - Cui, Miaomiao; Wang, Zuankai; Wang, Bin (Frontiers in Materials, 2022)
Corrosion is ubiquitous, inevitable, and very common in our daily lives; it has been one of the most significant challenges and needs to be addressed for the development of modern society. Corrosion-resisting strategies found in nature have been promising for many halophytes surviving in marine tidal zones facing high salinity and humidity. Among the halophytes, mangroves have developed a lot of functions to deal with such extreme conditions that could provide novel inspirations for the fabrication of engineering materials, especially for materials resisting corrosion. In this study, we first investigated two survival strategies of mangroves, namely, functional salt-secreting and mangrove tannin composite. Salt-secreting realized by mangrove salt glands could make mangroves excrete excessive salt and avoid harmful effects. On the other hand, mangrove tannins existing in large quantities in mangrove bark could help the mangroves survive some marine bacteria. Inspired by the functional mangrove tannins, we developed a corrosion inhibitor to protect Q235 carbon steel in acid 3.5 wt% NaCl solution. Furthermore, we found that the mangrove-inspired corrosion inhibitor could be adsorbed at the metal–solution interface, functioning as a cathodic inhibitor with 60.51% anti-corrosion efficiency.